Pemeriksaan Fisioterapi Pada Kemampuan Activity Daily Living (ADL) Lansia di Panti Jompo KNDJH Wonokoyo Malang - Anisa Husnia; Nurul Aini Rahmawati; Lisna Lisna (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
The Elderly is a stage where organs reach a process of decreasing size and function over time. The elderly's ability to carry out daily activities and measure independence can be done with an Activity Daily Living (ADL) examination. ADL is an activity carried out routinely daily and included in the main activities of self-care. ADL is one of the benchmarks for assessing functional capacity by asking questions about daily activities. The purpose of the examination was to find out and identify the number of elderly people with a level of independence and dependence in the KNDJH Wonokoyo nursing home. The method used is to carry out physiotherapy examinations regarding ADL using the Katz index instrument. The results obtained mostly have a level of total independence to the lightest dependence. However, some elderly people have a level of mild dependence to full dependence.